PENGARUH KOMPLEKSITAS OPERASI PERUSAHAAN DAN KOMITE AUDIT TERHADAP AUDIT DELAY DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2018 - Yoosita Aulia (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
This study aims to analyze and prove financial distress is able to moderate the influence of the audit committee and audit committe on audit delay. The population in this study are mining companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The sampling technique uses a purposive sampling technique with a total of 66 samples. The analysis technique used in this study is logistic regression. The results of this study indicate that . Financial distress does not moderate the effect of the complexity of the company's operations on audit delay on mining companies listed on the Indonesia Stock Exchange during the period 2016-2018. Financial distress does not moderate the effect of the audit committee on audit delay on mining companies listed on the Indonesia Stock Exchange during the period 2016-2018.